2020
DOI: 10.14202/vetworld.2020.1719-1724
|View full text |Cite
|
Sign up to set email alerts
|

Development of a coagglutination kit as a rapid test for diagnosing Newcastle disease in poultry

Abstract: Background and Aim: Newcastle disease (ND) is a viral infection that causes high mortality and economic loss in the poultry industry. The Office International des Epizooties (OIE) recommends several diagnostic methods for the detection of ND, including isolation and molecular tests. However, these detection methods are time-consuming and highly expensive. Therefore, this study was conducted to develop a coagglutination kit as a novel diagnostic tool for ND in the poultry industry. Materials and Methods: Two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The previous study described that utilization of polyclonal antibody produced by rabbit vaccination could be used as coagglutination kit with high sensitivity for diagnosing ND in poultry (Naf'an et al, 2020) and diagnosing viral nervous necrosis in fish (Sulistiyono et al, 2020). The findings of the present study indicated that ND polyclonal antibodies produced by vaccination can be used as the primary polyclonal antibody in chickens' tissue staining.…”
Section: Resultssupporting
confidence: 49%
“…The previous study described that utilization of polyclonal antibody produced by rabbit vaccination could be used as coagglutination kit with high sensitivity for diagnosing ND in poultry (Naf'an et al, 2020) and diagnosing viral nervous necrosis in fish (Sulistiyono et al, 2020). The findings of the present study indicated that ND polyclonal antibodies produced by vaccination can be used as the primary polyclonal antibody in chickens' tissue staining.…”
Section: Resultssupporting
confidence: 49%
“…Briefly, S. aureus was incubated using 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) and thermally treated at 65 °C for 30 min to reach an unculturable red-fluorescent state. The anti-GCA mAb was conjugated onto the red-colored S. aureus by the binding between the Fc fragment of the mAb and protein A on S.…”
Section: Methodsmentioning
confidence: 99%
“…When designing an RT-PCR technique, it's crucial to keep in mind a number of critical processes. A first step is the isolation of RNA (Naf'an et al, 2020). Using polymerase enzymes, PCR works on the premise that it can simultaneously amplify and distinguish between many target nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…However, the viruses of interest in this research contain RNA as their nucleic acid, thus PCR cannot be used. Since viral RNA serves as a template for reverse transcription, a particular Alyaa Mohson Reda, et al: Analysis of a Fragment of the Fusion Gene for Newcastle Disease by DNA Sequencing oligonucleotide primer and viral RNA must be used to generate single-stranded complementary DNA (cDNA) (Naf'an et al, 2020). Due to the rapid turnaround time, molecular methods have become more popular for identifying NDV infection.…”
Section: Introductionmentioning
confidence: 99%